2022
DOI: 10.1007/s41403-022-00335-1
|View full text |Cite
|
Sign up to set email alerts
|

Field Experiments to Identify and Eliminate Recirculation Zones to Improve Indoor Ventilation: Comparison with CFD

Abstract: Ventilation of shared indoor spaces is crucial for mitigating air-borne infection spread among its occupants. Replacing the air in a room with fresh air is key to minimize the concentration of potentially infectious aerosol generated in the room. Recirculating air flow present at corners and around obstacles can trap air and infectious aerosol. This can significantly delay their evacuation by the ventilation system. Knowing the location and extent of such recirculation zones is, therefore, important. In this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…1 b. These vortical structures have been reported in vertical airflow dispersion systems as Mixing Ventilation (MV) and Displacement Ventilation (DV) studied by Liu et al (2022a) and horizontal airflow extraction schemes by Sinha et al (2021 , 2022 ).
Fig.
…”
Section: Physical Fundamentalsmentioning
confidence: 70%
See 1 more Smart Citation
“…1 b. These vortical structures have been reported in vertical airflow dispersion systems as Mixing Ventilation (MV) and Displacement Ventilation (DV) studied by Liu et al (2022a) and horizontal airflow extraction schemes by Sinha et al (2021 , 2022 ).
Fig.
…”
Section: Physical Fundamentalsmentioning
confidence: 70%
“…Then Sinha et al (2021) concluded that increasing the flow rate does not eliminate the formation of recirculation regions, and they recommended that such regions should be identified in the room. Furthermore, Sinha et al (2022) suggested the elimination of the recirculation zones to improve ventilation by geometry modifications. Crowley et al (2022) performed an experimental and numerical study of non-evaporating droplet (10 to 200 μm) dispersion by flow nasal in a room (3 × 2 × 2 m) under MV, according to the configuration of inlet and outlet ports.…”
Section: Particle Dispersion Patternsmentioning
confidence: 99%
“…This may indicate that the room lacks a good air mix, as mentioned by CDC (2023). Such recirculating air flow, generally in the corners of the room and around furniture, can trap air and infectious aerosol, delaying its evacuation through the exhaust system (Sinha et al, 2022). This situation can be harmful to both the patient and the healthcare service providers.…”
Section: Diagnoses and Recommendationsmentioning
confidence: 99%
“…However, the virus’s airborne transmission during inhalation is still a significant concern in indoor environments, for example, workplaces, offices, elevators, schools, and colleges (Sinha et al. 2022 ; Sen 2021 ; Liu et al. 2021 ).…”
Section: Introductionmentioning
confidence: 99%